Earnings Management Before, During and After Covid-19 Period in the Hotels and Tourism Subsector Subsector Listed on the Indonesian Stock Exchange - Syahputri, Widia Dwi; Midiastuty, Pratana Puspa; Suranta, Eddy; Putra, Danang Adi (Yayasan Ilomata, 2024)
Covid-19 has an impact on the decline in firms performance. Several previous studies have found that companies strive to sustain performance through earnings management practices. Earnings management that can be performed in a company includes accrued earnings management and real earnings management. Previous studies have only focused on the differences in earnings management during the pandemic using accrual earnings management. So that in this study, apart from using accrual earnings management, it also adds real earnings management. This study aims to offer empirical insight into variations in earnings management during the Covid-19 period. This duration is divided into three distinct phases: pre, during, and post-Covid. Focusing on the 2017-2022 timeframe, this study specifically examines companies in the hotels and tourism subsector. The hypothesis was tested with a paired sample t-test. The findings showed no disparity in accruals earnings management in the pre, during, and post-Covid periods. However, the analysis showed significant differences in abnormal real earnings management related to production and discretionary factors before, during, and after the Covid-19 outbreak. Notably, abnormal real earnings management in production remains consistent before and after, as well as during and after the pandemic. In addition, discretionary abnormal real earnings management shows no difference before and during Covid-19 or during and after the pandemic. The practical implication is that post-Covid-19 pandemic firms actually carry out higher real earnings management as an effort to maintain or as a result of the decline in firms performance during the Covid-19 pandemic.